Pre-service teachers’ self-efficacy in implementing inclusive practices and resilience in Finland - Yada Akie; Björn Piia Maria; Savolainen Pirjo; Kyttälä Minna; Aro Mikko; Savolainen Hannu (Elsevier, 2025)
This study aims to explore Finnish pre-service teachers' self-efficacy in implementing inclusive education and their resilience. Survey data were collected from 105 pre-service teachers studying in a teacher education programme in one university in Finland. The relationships between pre-service teachers' self-efficacy in implementing inclusive practices, their perceived resilience, and background variables were examined using structural equation modelling. The results confirmed a three-factor structure for self-efficacy in implementing inclusive practices among the pre-service teachers. In addition, pre-service teachers’ self-efficacy was the strongest variable that related to their resilience. The findings would be beneficial for developing pre- and in-service teacher education.